Video DURASI (Edukasi Cara Menyusui or Education on How to Breastfeed) to Improve Breastfeeding Skills in Postpartum Mothers - Annisa Puteri Raka; Yuliasti Eka Purnamaningrum; Hesty Widyasih (CV Media Inti Teknologi, 2024)
This research aims to determine the effect of video DURASI on the breastfeeding skills of postpartum mothers. Kulon Progo ranks second and lowest in exclusive breastfeeding coverage in D.I. Yogyakarta and does not meet the WHO and the Ministry of Health targets. One of the causes found is the ineffective skills of postpartum mothers in breastfeeding. To find out the influence of Breastfeeding Education video media called DURASI (Edukasi Cara Menyusui or education on how to breastfeed) on the breastfeeding skills of postpartum mothers. This study is a quasi-experiment pre-test and post-test control group design with purposive sampling. The population in this study is postpartum mothers at Nyi Ageng Serang Hospital, Kulon Progo. Samples from 60 postpartum mothers were selected to be allocated into the experimental group (n1=30) and the control group (n2=30). The bound variable is the breastfeeding skills of postpartum mothers. The independent variable is breastfeeding education video media. Breastfeeding skills were measured by a checklist questionnaire. Breastfeeding skills between the two groups were tested with Mann-Whitney. The level of breastfeeding skills of postpartum mothers after being treated in the experimental group was 93.3% while the control group was 53.3%. There is an influence of video DURASI as breastfeeding education media on the breastfeeding skills of postpartum mothers. There were significant differences between the experimental group and the control group.